A historical analysis of Melami-Bayrami hagiographies - Erken, Ali. (Thesis (M.A.)-Bogazici University. Institute for Graduate Studies in Social Sciences, 2009., 2009)
This study analyzes three Melâmî-Bayrâmî menâkıbnâmes (hagiographies) written between the seventeenth and eighteenth centuries: Sarı Abdullah’s Semerâtü’l-Fuâd (c.1613), Lalizâde Abdülbâki’s Sergüzeşt (c.1740) and Müstakimzâde’s Menâkıbnâme-i Bayramiyye (c. 1750). The seventeenth century was a transformative period for the order in two senses. First, responding to the persecutions of the sixteenth century, Melâmî-Bayrâmî sheikhs increasingly preferred to hide their Melâmî-Bayrâmî affiliation and took refuge in other orders. Second, despite their earlier troubles and their newly increased secrecy, the order was able to spread into new social milieus and gain adherents among the ruling elites in İstanbul and the Balkan cities. This study argues that the dual transformation of the Melâmî-Bayrâmî order in this period marked its influence also on these hagiographies. Despite some differences between the contexts of the three texts, all three were written by the members of the Ottoman learned elite with ties to the ruling establishment, and all three represented an effort to project a considerably sanitized image of the Melâmî-Bayrâmîs. This thesis explores this sanitized image by looking specifically at how the three texts represent Melâmî-Bayrâmî sainthood, the relationship between Melâmî-Bayrâmîs and the other sufi orders and the persecution of Melâmî-Bayrâmîs in the preceding decades.
Keywords: Islamic hagiography -- History and criticism.